(untitled) (Engrami, 2022)
Introduction: According to the WHO, depression is a common mental disorder where workplace conditions play a significant contributing factor. Objective: To examine the prevalence of depression and the relationship with sociodemographic characteristics in staff at the Institute for Emergency Medical Services (EMS) Belgrade, i.e., physicians, medical technicians, drivers and administrative workers. Methodology: The research was conducted at the City Institute for EMS Belgrade in the period from December 1 to December 6, 2007. The questionnaire consisted of questions about the sociodemographic characteristics of participants, a self-assessment questionnaire for depression PHQ-9 and a question about the use of antidepressants. The data that was collected was statistically processed with the software package SPSS 20.0 Results: The study included 118 participants, 58.47% were male and the average age was 40.77 ± 8.86. The result of the PHQ-9 test showed that 30% of the participants had subsyndromal depression, 11% had a mild depressive episode, most often in female participants (p = 0.023) and in administrative workers (p = 0.003). Depression was present in 16.95% of respondents. Out of the 9 listed symptoms of depression, fatigue/extreme exhaustion were most commonly present (47.46%) as well as feelings of emptiness and hopelessness (43.22%). Only 11.86% of participants used antidepressants and there was no statistically significant difference in relation to the observed parameters. Conclusion: Subsyndromal depression is significantly present among the EMS staff in Belgrade, more often among female participants and those working in administration.